APX001 Pharmacokinetic/Pharmacodynamic Target Determination against Aspergillus fumigatus in an In Vivo Model of Invasive Pulmonary Aspergillosis - Zhao, Miao (Antimicrob Agents Chemother, 2019)
APX001, the prodrug of APX001A, is a first-in-class antifungal agent that has a potent activity against Aspergillus fumigatus. The goal of current study was to determine the pharmacodynamic (PD) index and target of APX001 in an immunocompromised murine model of invasive pulmonary aspergillosis against 6 A. fumigatus isolates. Minimum effective concentration (MEC) values ranged from 0.03 to 0.06 mg/liter. Dose fractionation was performed against isolate AF293 using total doses of APX001 ranging from 81 to 768 mg/kg of body weight/day fractionated into every 3-, 6-, and 8-h regimens over a 96-h treatment duration. Efficacy was assessed by A. fumigatus quantitative PCR (qPCR) of conidial equivalents from lung homogenates. Nonlinear regression analysis using the Hill equation demonstrated that the 24-h area under the concentration-time curve (AUC)/MEC ratio was the pharmacokinetic (PK)/PD index that best correlated with efficacy (coefficient of determination [R(2)] = 0.79). Treatment studies with the remaining strains utilized regimens of 40 to 1,536 mg/kg of APX001 administered every 3 h for a 96-h duration. Exposure-response relationships for all strains were similar, and the median free drug AUC/MEC PK/PD targets for stasis and 1-log-kill endpoints were 47.6 and 89.4, respectively. The present studies demonstrated in vitro and in vivo APX001A/APX001 potency against A. fumigatus. These results have potential relevance for clinical dose selection and evaluation of susceptibility breakpoints.